PENERAPAN PRAKTIKUM BERBASIS INKUIRI UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA - Rahmawati, Ria; Haryani, Sri; -, Kasmui (Universitas Negeri Semarang, 2014)
Practicum taken place in schools is still verification, just to prove a concept or principle Â that has been previously studied, resulting in not developing science process skills. Therefore, learning strategy is required to improve the students' science process skills by inquiry-based lab methods. This study aimed to obtain information science process skills improvement class X after applying the inquiry-based lab hydrocarbon material. The study used a quasi-experimental method with a pretest-posttest control group design. Science process skills were measured using written tests and observation. The results show the value of KPS experimental class better than the control class. Measurements obtained by testing the highest increase in the experimental class and control class in predicting indicators, while the lowest increase in the experimental class and control class hypotheses indicator on the indicator hypothesis. Through observation of KPS, obtained the highest increase in the experimental class and control class observing indicators on communication indicator, while the lowest increase in the experimental class on asking questions and the control class on classification indicator. The results of KPS showed the increase of experimental class higher than the control class. Students give positive response to the inquiry-based learning lab at the hydrocarbon material because it gives students the chance to participate actively, and increase student motivation. Based on studies, it concluded that lab-based inquiry can improve the students' KPS. Keywords: Inquiry, Science Process Skills, Practicum